Molecular and Clinical Significance of Fibroblast Growth Factor 2 in Development and Regeneration of the Auditory System - Jeong, Minjin; Bojkovic, Katarina; Sagi, Varun; Stankovic, Konstantina M. (Frontiers in Molecular Neuroscience, 2021)
The fibroblast growth factor 2 (FGF2) is a member of the FGF family which is involved in key biological processes including development, cellular proliferation, wound healing, and angiogenesis. Although the utility of the FGF family as therapeutic agents has attracted attention, and FGF2 has been studied in several clinical contexts, there remains incomplete understanding of molecular and clinical function of FGF2 in the auditory system. In this review, we highlight the role of FGF2 in inner ear development and hearing protection, and present relevant clinical studies for tympanic membrane (TM) repair. We conclude by discussing the future implications of FGF2 as a potential therapeutic agent.